Case Study: The Graduates of the Theological Department of the EKPA Evaluate the Effectiveness of Their Studies - Grilis, Georgios (Greek Journal of Religious Education (GjRE), 2025)
There is more talk in recent decades about the effectiveness of the Curriculum of university institutions, as well as their ability to equip their graduates with the necessary skills. In particular for theological studies, the E.U. in the framework of the Tuning Project, a pan-European program for Higher Education, it proposed a series of skills necessary for theologians of the 21st century. The present study targeted graduates of the Department of Theology, School of Theology at the National and Kapodistrian University of Athens (NKUA) during the academic year 2021–22, aiming to explore how the graduates of the Department of Theology at NKUA evaluate their studies. Of the 161 graduates, 80 responded (49.69%). The findings of the research were presented to the Rrogram Committee of the Department and formed the basis of discussion for the new Curriculum which will be implemented from the next year.